2021
DOI: 10.1111/ans.16847
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surgical management for phaeochromocytoma over a 17‐year period: an Australian perspective

Abstract: Background: Minimally invasive adrenalectomy and advances in anaesthetic techniques have transformed surgery for phaeochromocytoma. This 17-year review describes the evolution of phaeochromocytoma care in our unit. Methods: We performed a retrospective cohort review of all patients who underwent adrenalectomy for phaeochromocytoma from 2000 to 2016. Patients were divided into three time periods, early: 2000-2005 (n = 17), middle: 2006-2010 (n = 15) and late: 2011-2016 (n = 24). The posterior retroperitoneoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…However, the rate of complications is widely variable among series, ranging from 10-40% [8][18] [11] [19]. There are several plausible explanations for this wide range, including referral biases, differences in the de nition of complications and in the type of complications reported, and importantly, the decade of the performed research as it is known that a signi cant reduction in pheochromocytoma surgical treatment morbidity and mortality has taken place over recent decades [20]. In agreement with our study, series evaluating the severity of complications found similar gures of grade III and IV complications in the Clavien-Dindo score [10][9] [11], although in some series severe complications occurred in up to 31% of the cases [8].…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…However, the rate of complications is widely variable among series, ranging from 10-40% [8][18] [11] [19]. There are several plausible explanations for this wide range, including referral biases, differences in the de nition of complications and in the type of complications reported, and importantly, the decade of the performed research as it is known that a signi cant reduction in pheochromocytoma surgical treatment morbidity and mortality has taken place over recent decades [20]. In agreement with our study, series evaluating the severity of complications found similar gures of grade III and IV complications in the Clavien-Dindo score [10][9] [11], although in some series severe complications occurred in up to 31% of the cases [8].…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…This incidence was similar to other studies (2.0%-8.5%) 7,8,13,15,23 and presented transiently as abdominal wall laxity, pain or sensory changes. 7,15,23 By avoiding breaching the peritoneum, PRA may offer reduced post-operative pain, 11,15 and account for no post-operative ileus being observed. Haemorrhage or haematoma occurred more commonly after TPA (1.8%) than PRA (0.4%), and triggered conversion in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…High insufflation pressure (20 mmHg) in the retroperitoneal space may contribute to a lower risk of PRA conversion due to bleeding. 11,13,14 However, venous compression may contribute to VTE formation after PRA (1.3%). This contradicts studies reporting 0% incidence following PRA 13,15,20 and occurring after TPA only (0.4%-1.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations